Rebalancing in China-Progress and Prospects - Zhang, Longmei (IMF Working Papers; Working Paper ;, 2016)
China is transitioning to a greener, more inclusive, more consumer and service based, and less credit-driven economy. This paper defines a framework for assessing rebalancing, reviews progress, and discusses medium-term prospects. External rebalancing has advanced well, while progress on internal rebalancing has been mixed, with substantial progress on the supply side, moderate progress on the demand side, and limited progress on the credit side. Rebalancing on income equality and environment has also been mixed, with the energy intensity of growth falling and labor's share of income rising, but income inequality and local air pollution remaining very high. Going forward, the high national saving is expected to fall owing to demographic change and a stronger social safety net, while the investment ratio is expected to fall similarly, with increasing competition and profit normalization as growth slows. The service sector will continue to gain importance, helping reduce the carbon intensity of output and increase labor's share of national income and household consumption. Reducing the credit intensity of growth is likely to progress slowly unless decisive corporate restructuring and SOE reforms are implemented.